Strategi Branding dan Digital Marketing untuk Penguatan Promosi Wisata Hiu Gorontalo Berkelanjutan - Mohamad Afan Suyanto; Anggita Permata Yakup; Olfin Ishak; Yakup Yakup; Deby Rita Karundeng (Universitas 45 Surabaya, 2025)
Marine tourism has become one of Gorontalo’s key attractions, particularly through the whale shark sightings in Botubarani Village. However, existing branding efforts and digital promotion have not yet captured the region’s local strengths effectively. This community engagement program was carried out to formulate a branding strategy that highlights conservation, cultural values, and the unique character of Gorontalo’s shark tourism, while also enhancing the community’s digital promotion skills. The study employed a participatory qualitative approach through outreach activities, training sessions, focus group discussions, and mentoring involving 40 participants from various community groups. Data were collected through observation, simple questionnaires, and documentation, and were analyzed using a SWOT framework. The results show that a strong destination brand can be developed through three main pillars: whale shark conservation, strengthening local culture, and advancing coastal MSME products. Digital training significantly improved the community’s ability to produce photo, video, and narrative content, making the village’s social media more active and well-directed. The SWOT analysis produced practical strategies that stakeholders can apply to reinforce the destination’s identity. These findings emphasize that conservation- and culture-based branding, supported by digital marketing, can enhance community participation and strengthen the competitiveness of marine tourism in a sustainable manner.